Pengembangan Bahan Ajar Berbasis E-Learning Mata Kuliah Fisika Dasar pada Jurusan Biologi FMIPA UNM - Agung, Afiq; Amin, Bunga Dara; Yani, Ahmad; Swandi, Ahmad (Indonesian Journal of Educational Studies, 2018)
This study develops instructional materials in the form of textbooks and is packaged in the form of e-Learning. The material that was raised was Fundamental Physics devoted to Department of Biology FMIPA UNM. This is a Research and Development research with 3D model (define, design and development). The results showed that the validation of teaching materials and materials in teaching materials included in the category is â€œvery goodâ€. The practitioners 'assessment showed that the basic physics teaching materials based on e-learning were included in the "very good" category while the students' perceptions of the Teaching Materials were included in the "good" category. Thus e-learning materials based on fundamental physics materials for biology department worthy of use in the process of learning in fundamental physics courses in biology department.